Sustainable Agricultural Economics: A Systematic Literature Review and Bibliometric Analysis - Rut Normasari; Stenly Kawuwung; Shapely Ambalao (Economics and Digital Business Review, 2026)
Sustainable agricultural economics has emerged as an increasingly important research field in response to global challenges such as climate change, environmental degradation, food insecurity, and resource scarcity. Despite the growing volume of scholarly publications, the existing literature remains fragmented across multiple themes, methodologies, and disciplinary perspectives, limiting comprehensive understanding of the field’s intellectual structure and future research directions. Therefore, this study aims to: (1) examine whether sustainable agricultural economics continues to be a significant area for future academic inquiry, (2) analyze the current research landscape and distribution within the field, and (3) identify key theoretical and practical implications for advancing future research. This study employs a combined Systematic Literature Review (SLR) and bibliometric analysis approach following the PRISMA 2020 framework. Data were collected from the Scopus database in May 2026 using structured keyword combinations related to agricultural economics and sustainability. Bibliometric mapping was conducted using VOSviewer to analyze publication trends, geographical distribution, institutional productivity, journal sources, authorship patterns, and keyword co-occurrence networks. Additionally, thematic analysis was applied to identify dominant research themes and emerging scholarly trends. The findings reveal that sustainable agricultural economics is a rapidly expanding and highly relevant field of academic inquiry. Publication trends demonstrate significant growth from only two publications in 1989 to 186 publications in 2025 and 161 publications in 2026. China emerged as the dominant contributor in terms of publication output and institutional productivity, while leading journals included the Journal of Environmental Management and the Journal of Cleaner Production. Thematic analysis indicates that the literature is increasingly focused on sustainable development, agricultural sustainability, economic analysis, crop production, circular economy practices, and technological innovation such as precision agriculture and digital farming systems. The study concludes that sustainable agricultural economics has evolved into a multidisciplinary and strategically important research domain integrating economic performance, environmental sustainability, technological adaptation, and social resilience. Future research should further explore sustainability governance, policy effectiveness, financial mechanisms, socio-economic inclusiveness, and climate-resilient agricultural systems to strengthen sustainable global food systems and long-term agricultural development.